Menopause Depression Management Through Self-Esteem Development - Sarika Ashish Ghate; Vikas S Minchekar; Dean Zulmi Airlangga (‎‎‎TAZKIYA Journal of Psychology, 2023)
In our culture, it is an established myth that menopausal depression is normal for every woman. However, the fact can differ from this common misconception. Women who suffer from it go through dramatic mental changes. Hence, she should get the same attention as any other medical illness. In this study, the researcher tried to find ways to decrease menopausal depression by fostering her self-esteem. The study aimed to find the correlation between depression and self-esteem during menopause among women. A sample of 30 women was collected by purposive sampling from Kolhapur City. The selfesteem scale developed by Singh and Srivastava and depression scale developed by Thakur and Singh were administered to the sample. After calculating row scores, the correlation was found using the product moment method. A negative and significant correlation was found between depression and selfesteem. So women who have high self-esteem will have a low level of depression, and vice versa if the self-esteem is low, the woman will quickly feel depressed.